MODERASI BERAGAMA PERSPEKTIF AHMAD AL-SHAWI: Telaah atas Penafsiran QS. Al-Baqarah [2]: 143 dalam Tafsir Al-Shawi - Syachrofi, Muhammad; Alby Saidy El Alam (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2023)
There are many factors that influence the occurrence of acts of violence in the name of religion. One of them is the misreading of religious texts, giving birth to a single perspective. To overcome this, it is necessary to review how the Qur'an in essence teaches religion in moderation. Therefore, this article will discuss about religious moderation in the Qur'an perspective of Ahmad al-Shawi. He is one of the mufasir whose work is quite influential in Indonesia. Most Islamic boarding schools in Indonesia use Tafsir al-Shawi as a reference in studying Qur'anic tafsir. This research focuses on al-Shawi's interpretation of QS. Al-Baqarah [2]: 143 is a verse that is often associated with the foundation of religious moderation. This research is qualitative research using descriptive-analytical methods. The results showed that ummah wasath referred to in QS. Al-Baqarah [2]: 143 is a person who has a moderate attitude characterized by several criteria, namely fair, commendable character, knowledge, and practicing his knowledge.